2016
DOI: 10.1080/03019233.2016.1219183
|View full text |Cite
|
Sign up to set email alerts
|

Silicon volatilisation in the form of SiO during slagging by limestone in BOF

Abstract: In this paper, the silicon volatilisation phenomenon during slagging by limestone in basic oxygen furnace (BOF) and its influencing factors were studied by industrial experiment and thermodynamic calculation. In our estimation, the volatilisation ratio of silicon in this industrial experiment is about 13.01-47.82%. Thermodynamic analysis showed that the silicon volatilisation phenomenon happens after charging limestone directly into BOF because CO 2 from limestone decomposition could massively oxidise the sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The high-melting point 2CaO•SiO 2 layer formed at the surface of lime is one of the limiting factors that affect lime dissolution [5], and the formation of 2CaO•SiO 2 layer could be hindered by increasing the value of FeO/SiO 2 in slag [6]. On the basis of long-term laboratory studies, University of Science and Technology, Beijing, proposed a process of using limestone to substitute lime to slag in BOF [7,8]. By charging limestone directly into BOF for slagging, the traditional 'calcination in lime kilns → lime slagging in BOF' process has been simplified to 'limestone slagging in BOF' process.…”
Section: Introductionmentioning
confidence: 99%
“…The high-melting point 2CaO•SiO 2 layer formed at the surface of lime is one of the limiting factors that affect lime dissolution [5], and the formation of 2CaO•SiO 2 layer could be hindered by increasing the value of FeO/SiO 2 in slag [6]. On the basis of long-term laboratory studies, University of Science and Technology, Beijing, proposed a process of using limestone to substitute lime to slag in BOF [7,8]. By charging limestone directly into BOF for slagging, the traditional 'calcination in lime kilns → lime slagging in BOF' process has been simplified to 'limestone slagging in BOF' process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the CO 2 generated from the decomposition of limestone in the converter can react with the elements in the hot liquid iron to generate CO, which increases the amount of gas recovery and the concentration of CO [10][11][12][13]. Mao et al confirmed through industrial tests that the slagging of limestone in the converter can lead to the volatilization of some silicon elements in the hot liquid iron, thus reducing the amount of slag [14][15][16]. Moreover, during the decomposition of limestone in the converter, the CO 2 produced can not only be used as part of the endogenous oxygen source to replace oxygen in the steelmaking reaction, but the escape of CO 2 can also lead to the improvement of the molten pool kinetic conditions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%